Intermittent aeration of landfill simulation bioreactors: Effects on emissions and microbial community. (November 2020) - Campanaro, Stefano; Raga, Roberto; Squartini, Andrea
Highlights: Intermittent running proves effective in emission control during landfill aeration. Landfill microbiome responding to different landfill aeration regimes. Identification of microbial genomes involved in landfill simulation experiments. Role of microbial species in ammonia oxidation and methane production. Abstract: Landfill simulation experiments were run at lab-scale to compare the effects of intermittent and continuous aeration on the evolution of leachate composition and biogas production. The experiments were carried out using six reactors; two of them under continuous aeration, two under intermitted aeration and two anaerobic as a control. Different aeration regimes produced different effects on reactors. As expected, carbon discharge via biogas was higher in reactors under continuous aeration than under intermittent aeration. The evolution of leachate quality was affected by the aeration regimes; however, at test end very similar concentration were ascertained for relevant leachate parameters in all aerated reactors. A comprehensive description of the aerobic and anaerobic landfill microbiome is provided, using a metagenomic approach focused on the microbial genome reconstruction. A time course investigation evidenced the modification of the microbiome and revealed taxa and specific microbes more strictly connected to the environmental parameters of the reactors. Methanoculleus, Syntrophomonas and Parabacteroides were identified as the genera more strictly connected to biogas production, while numerous species belonging to Thiomonas, Nitrosomonas, Xanthomonadaceae, Myxococcales and Alcaligenaceae were found to be connected with NH4 + oxidation.